2017
DOI: 10.1002/jrs.5090
|View full text |Cite
|
Sign up to set email alerts
|

Polymorph formation in fenofibrate in the absence and presence of polymer stabilizers: a low wavenumber Raman and differential scanning calorimetry study

Abstract: In situ, variable temperature low wavenumber Raman spectroscopy and differential scanning calorimetry together with scanning electron microscope imaging were used to investigate polymorph formation in the non-hydrogen bonded, anti-cholesterol drug fenofibrate (FNB), in the absence and presence of two non-ionic polymeric stabilizers: triBlock copolymer pluronic-F127 (PF/127) and hydroxypropyl methyl cellulose (HPMC/E3).Low wavenumber Raman spectra show that metastable phase II formation occurs on initial coolin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Ying et al studied polymorph formation in the anticholesterol drug fenofibrate (FNB) in the absence and presence of polymer stabilizers by low wavenumber Raman and differential scanning calorimetry. Their results were discussed in terms of molecular simulations carried out to determne the nonbonded interaction energies between the polymers and FNB . Zhang, Sha, and Wang used laser perturbation two‐dimensional correlation Raman spectroscopy for assessing quality control of bovine colostrum products.…”
Section: Pharmaceutical Food and Forensic Applicationsmentioning
confidence: 83%
See 1 more Smart Citation
“…Ying et al studied polymorph formation in the anticholesterol drug fenofibrate (FNB) in the absence and presence of polymer stabilizers by low wavenumber Raman and differential scanning calorimetry. Their results were discussed in terms of molecular simulations carried out to determne the nonbonded interaction energies between the polymers and FNB . Zhang, Sha, and Wang used laser perturbation two‐dimensional correlation Raman spectroscopy for assessing quality control of bovine colostrum products.…”
Section: Pharmaceutical Food and Forensic Applicationsmentioning
confidence: 83%
“…Their results were discussed in terms of molecular simulations carried out to determne the nonbonded interaction energies between the polymers and FNB. [199] Zhang, Sha, and Wang used laser perturbation two-dimensional correlation Raman spectroscopy for assessing quality control of bovine colostrum products. Their results showed that the correlation coefficients between each bovine colostrum product with their mean value 0.991 ± 0.003, which indicated that there were high similarities between these products.…”
Section: Liquids Solutions and Liquid Interactionsmentioning
confidence: 99%
“…The Raman spectrum also supports that the fenofibrate nanocrystals are form I polymorph (Figure 3c and Figure S11b, Supporting Information). [ 41,42 ] DSC analyses not only suggest the presence of fenofibrate nanocrystals with a single endothermic peak of melting (Figure 3d) but also show a high degree of crystallinity (≈100% in Figure 3e) approximated with the prior knowledge of decreasing fusion enthalpy for lower melting points [ 34,43 ] (Section S11, Supporting Information). The Gibbs–Thomson equation predicts that melting point depression becomes more significant for smaller nanocrystals.…”
Section: Resultsmentioning
confidence: 99%
“…[101,102] Molecular simulations have shown that MC and HPMC have a strongly favorable energetic interaction with surfaces of hydrophobic APIs, including FEN, through hydrogen bonding. [103][104][105][106] Controlling intermolecular interactions during crystallization within hydrogel scaffolds could present an opportunity for polymorphic control, a long-desired goal of drug substance manufacturing. [107]…”
Section: Delayed Pulsatile Drug Release Can Be Programmed From Formul...mentioning
confidence: 99%